Ether-linked lipids of rat developing and adult epididymis - Luquez, Jessica Mariela (2016)
In mammalian tissues, glycerophospholipids (GPL) and tri-glycerides (TG) occur in three sublcasses, depending on wheth-er the chain at the sn-1 position of the glycerol backbone is a fatty acid, a fatty alcohol, or a fatty aldehyde. This study fo-cused on the ether-linked (EL) subclasses of GPL and TG, fol-lowing their changes during postnatal development in rat epidi-dymis and, in the adult, their distribution among epididymal caput, corpus and cauda regions. At postnatal day 30, in a still scarcely differentiated epithelium lacking spermatozoa, the epididymis already contained plasmanyl- and plasmenyl-ethanolamine (Pls-Et) with 22:4n-9 (DTA), the DTA-containing plasmenyl-choline (Pls-Cho) increasing with development and the presence of sperm. In the adult tissue, the DTAPls-Et con-centration per mg protein was highest in the corpus and higher than that of DTA-Pls-Cho in the three epididymal regions, sug-gesting a precursor-product relationship. The latter subclass is in turn the one to increase the most in rat spermatozoa as they mature. The epididymal EL-TG were even richer in DTA than the GPL, the 1-alkyl- predominating over the 1-alk-enyl- sub-class at all ages, their concentration being highest in the corpus. These results correlated well with the expression (mRNA) of a key peroxisomal enzyme involved in the biosyn-thesis of these lipids, alkylglycerone phosphate synthase.